2020
DOI: 10.21203/rs.2.16687/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Indole -3-acetic acid improves drought tolerance of white clover associated with activating auxin-related genes, abscisic acid and jasmonic acid-induced stress responsive transcription factors, and inhibiting senescence genes

Abstract: Auxin plays an important role in regulating plant development. To idenfity what effects IAA has in white clover under drought stress and how IAA regulates white clover response to drought. Relative water content, chlorophyll content, six phytohormones content, expression of gene-related to IAA signal perception and synthesis, transcription factor genes related to drought-resistance and senescence genes were investigated in white clover pretreated with 1µM exogenous IAA or 100µM L-AOPP (inhibitor of IAA synthes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
0
1
0
Order By: Relevance
“…Taking into account the effect of IAA and the general trend in the literature, this regulator might be able to decrease REL values under stress conditions in plants (Xing et al 2016;Zhang et al 2020). However, we observed that IAA did not cause any change in the REL value under salinity.…”
Section: Discussionmentioning
confidence: 89%
“…Taking into account the effect of IAA and the general trend in the literature, this regulator might be able to decrease REL values under stress conditions in plants (Xing et al 2016;Zhang et al 2020). However, we observed that IAA did not cause any change in the REL value under salinity.…”
Section: Discussionmentioning
confidence: 89%